Using the Transtheoretical Model of Change to Understand High School Students’ Hookah Smoking Behavior - Darya Subhi Ramadhan, Mohammed Baqer Habeeb, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective(s): The aim of this study is to understand high school students’ hookah smoking behavior. Methodology: Part of the study was an experimental randomized controlled trial used to guide this study. The study was carried out at Tuz High School for males in Tuz Khurmatu District, Salah-Aldeen Governorate. The study included a simple random sample of 144 high school students. The study instrument includes students’ sociodemographic data. It also includes the Stages of Change Scale for Hookah Smoking, The Processes of Change Scale for Hookah Smoking, The Self-Efficacy/ Temptation Scale for Hookah Smoking, and The Decisional Balance Scale for Hookah Smoking. Data were collected using a self-reported method for the period from November 1st, 2021 to March 31th, 2022. Data were analyzed using the statistical package for social science (SPSS) for Windows, version 26. Results: The study results revealed that more than two-fifth of subjects in the study group were in the Precontemplation Stages of Change, followed by those who were in the Contemplation, and those in the Preparation Stage of Change. The administered intervention made subjects use more Processes of Change, enhanced their Self-Efficacy and Decisional Balance of hookah smoking cessation. Conclusion: The Stage-matched intervention efficaciously made students use more Processes of Change of hookah smoking, enhanced their Self-Efficacy/Temptation of hookah smoking, and Decisional Balance of hookah smoking. The lower the Stage of Change, the poorer the Self-Efficacy for hookah smoking cessation.